Avaliação bromatológica de alimentação de Tamanduá-mirim (tamandua tetradactyla) em um zoológico - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Tamandua tetradactyla popularly known as anteater, is an insectivorous animal and feeds mainly on ants and termites. One of the biggest problems in keeping captive anteaters is the formulation of an adequate artificial diet, since nutrition is very important for the maintenance of life, from growth to reproduction. Therefore, the objective of this work was to analyze the bromatological composition of two diets supplied to the anteaters at the Municipal Zoo of Canoas, in Canoas, RS, and to compare them with the information already published for the species. The analyzes were carried out in the Laboratory of Bromatology of the Federal University of Pampa, Campus Dom Pedrito-RS, and the diets were evaluated for the composition of Dry Matter (DM), Crude Protein (CP), Crude Fiber (CF), Ethereal Extract (EE), ashes or Mineral Matter (MM), and weighted in duplicates, according to the Association of Official Analytical Chemists (AOAC, 1997). However, the crude protein (30.63% A, 30.94% B) and ethereal extract (10.15% A, 10.18% B) were different from those published in other studies. ) are within the requirements of anteaters in wildlife, while crude fiber obtained much higher levels (16.95% A, 21.49% B), which may influence the consumption and absorption of nutrients and mineral matter (1 , 36% A, 1.58% B) lower than the other studies, which should have greater attention since the deficiency of minerals can cause serious metabolic problems. Therefore, it is important to continue studies on the adequate nutrition of captive anteaters and other wild animals, since they need diets that meet their daily needs.
Keywords: Animais silvestres; Bromatologia; Nutrição; Wild animals; Bromatology; Nutrition; CNPQ::CIENCIAS AGRARIAS